(untitled) (Experimental biology, 2022)
Currently, there is a continuous growth of deposits in Western Kazakhstan that are in the late stage of development. Deposits often have a complex heterogeneous structure with hard-to-recover reserves, so for their effective development it is necessary to apply methods of increasing oil recovery. One of the most effective methods of enhanced oil recovery is microbial enhanced oil recovery (MEOR). Microorganisms of the developed oil-reservoir waters, adapted to the extreme underground conditions of the reservoirs, are promising objects for the development of microbiological methods for increasing oil recovery, based on their ability to displace and dilute oil. The article presents the identification of aerobic microorganisms, waterlogged oil reservoir waters of the Akingen field. The aim of this study was to identify microorganisms of oil-reservoir waters of the Akingen field isolated under aerobic conditions. Traditional microbiological and genetic methods of identification of microorganisms are used in the research work. The enzymatic activity of the isolated strains (lipase, amylolytic, proteolytic activity) was evaluated. The emulsification index was carried out according to the Cooper method. As a result of microbiological and genetic studies of the nucleotide sequence of the 16S rRNA gene fragment, 14 aerobic strains of microorganisms were identified as representatives of the genus Pseudomonas and Bacillus, in particular, Bacillus paramycoides-M1; B. subtilis subsp. spizizenii-S1; Bacillus sp. - M2, A1, A2, A3, A4, A5, S2, S3, D-1X; P. aeruginosa-D5, D6, D7. The evaluation of emulsifying activity allowed us to identify 4 strains of microorganisms with a high oil emulsification index: P. aeruginosa-D5, D6, D7 (40-49 %) and Bacillus sp. D1X (32 %). Isolates P. aeruginosa - D5, D6, D7 and Bacillus sp. D1X are promising objects for use in enhanced oil recovery technologies.